Perubahan Fonem pada Bahasa Jawa ngapak di Kabupaten Kebumen (Sebuah Kajian Fonologi) - Prapti Wigati Purwaningrum (LPPM Universitas Bina Sarana Informatika, 2018)
Abstract - The purpose of this analysis is to know some contributing factors of phonem changes in Bahasa Jawa ngapak in Desa Bendungan, Kabupaten Kebumen. The method of this analysis is field research and the data of this analysis are taken from some utterances which uttered by respondence. In collecting the data, writer interviewed the respondence about same words then write the fhonetic transcription of it. The writer found some phoneme changes such as coarticulation process in labialization in <tua> [tuwa], nasalisation [mb], [nd], and [nϯ], and glottalisation in [riʔ], [uɭaʔ], [sapaʔ]. The next changes are distribution process such as aferesis <hati> [ati], <hujan> [uϲan], <rumah> [umah], apokop<ular> [uɭaʔ], monophthong <danau> [dano] [au] menjadi [o], and the last process is anaftiksis such as paragog in <siku> [sikuʈ. Besides that the writer also found some consonants cluster in Bahasa Jawa Ngapak such as [swiwi], with [r] [kruŋu], [mripat], [mriɲaŋ], [srəŋɛŋɛ] with [l][bləϲuk], [gluduk], [blədɛg]. Some consonants also found in bahasa jawa ngapak Desa Bendungan kabupaten Kebumen [p], [b], [t], [ʈ], [ϲ], [ϯ], [k], [g], [ʔ], [m], [n], [ŋ], [ɲ], [r], [s], [j], [h], [w], [l]. Besidesthat some vocals also appear [i], [u], [e], [ə], [ɛ], [o], [a]. Keywords: perubahan fonem, konsonan, vokal, konsonan gabungan, bahasa Jawa ngapak kabupaten Kebumen.